ANALYSIS OF FACTORS CAUSING FLOODING IN PEOHO VILLAGE, WATUBANGGA DISTRICT, KOLAKA REGENCY - Ahmad Iskandar; Gaby Nanda Kharisma; I Ketut Suartini (Geographica: Science and Education Journal, 2025)
This study aims to analyze the factors causing flooding in Peoho Village, Watubangga District, Kolaka Regency. The type of research used in this study is descriptive research with qualitative and quantitative approaches. The data used in this study consists of rainfall data, soil type, slope gradient, land use, drainage system, flood control buildings and river conditions in Peoho Village. The data were collected using various methods including observation techniques, interviews, and documentation. Qualitative data were analyzed using qualitative data analysis according to Creswell. While quantitative data were analyzed using descriptive statistics. Based on the results of the study, the factors causing flooding in Peoho Village, Watubangga District, Kolaka Regency were caused by various factors, including moderate to high rainfall intensity. Another factor that causes flooding is the type of chromic latosol soil. This type of soil has a clay texture and small pores so that it quickly becomes saturated and water is difficult to absorb into the soil. The slope of the slope in Peoho Village which is dominated by flat and gentle slopes also contributes to the occurrence of flooding. Land use factors dominated by plantation land and a drainage system that does not function properly are also factors that cause flooding in Peoho Village.